AKTIVITAS ANTIRAYAP DARI EKSTRAK METANOL GUBAL KAYU GAHARU BUAYA (Aetoxylon sympetalum) TERHADAP RAYAP TANAH (Coptotermes sp.) (ANTITERMITE ACTIVITY OF METHANOL EXTRACT AGARWOOD BUAYA (Aetoxylon sympetalum) ON SUBTERRANEAN TERMITES (Coptotermes sp.)) - Khairunnisa Asyari; Afghani Jayuska; Muhamad Agus Wibowo; Puji Ardiningsih (Tanjungpura University, 2023)
Agarwood buaya (Aetoxylon sympetalum) is a Kalimantan endemic plant whose utilization has not been optimal. This plant has potential as an anti-termite, one of which is sapwood. This study aims to determine the content of secondary metabolites from the results of phytochemical screening, components of agarwood buaya sapwood based on GC-MS analysis fraction n-hexane and anti-termite activity against subterranean termites (Coptotermes sp.). Research that has been done is divided into four steps, maceration and fractionation, phytochemical screening, GC-MS analysis, and testing the activity of termites using a forced feeding test method. Crude methanol extract from 1 kg of dried agarwood buaya sapwood was 240.787 g (24.0787%), consisting of 0.8339% n-hexane fraction, 86.3663% chloroform fraction, and 0.7571% methanol fraction. The results of phytochemical screening on agarwood buaya sapwood extract showed that it contained flavonoid, terpenoid, steroid, and phenolic compounds. Identification of the components of agarwood buaya sapwood fraction n-hexane through GC-MS yielded compounds a4-chloro-6-methoxy-2-methylquinolin-8-amine (10.33%), stigmasterol among other (5.94%), n-hexa-decanoic acid (3.2%), 6-octa-decenoic acid (2.99%), and 1,2-Benzene-diol, 3,5-bis(1,1-dimethyl-ethyl) (2.01%). Termite activity test was carried out for 3 days with variations in the concentration of 0% (negative control), 0.1%, 0.2%, 0.3%, 0.4% (w/v), and 0.25% (v/v) (fibronil as positive control). The results of anti-termite testing show the most active fraction was the methanol fraction (LC50 0.146%) followed by the chloroform fraction (LC50 0.167%), methanol crude extract (LC50 0.192%), and the n-hexane fraction (LC50 0.208%).